Experimental study on the shear behaviour of high-strength lightweight concrete beams incorporating graphene oxide - Xiaojiang Hong; Jin Chai Lee; Bo Qian; Mingdong Yu; Qiansha Li; Panli You (Scientific Reports)
Abstract Graphene oxide (GO) has achieved significant progress in the material behaviour of cement-based materials. However, research on its structural behaviour in high-strength lightweight concrete (HSLWC) structures is limited, which restricts its engineering applications. This study focused on investigating the effects of low contents of GO on the shear behaviour of HSLWC beams. A total of four HSLWC beams with GO contents of 0, 0.01, 0.03 and 0.05% (by weight of cement) were designed to observe failure modes, load‒deformation curves, shear capacities, crack behaviour and load‒strain curves under four-point loading by a 300 kN servo loading device. The results revealed that all the beams exhibited shear compression failure. GO improved the shear capacity of the HSLWC beams, and this strengthening effect increased with increase in GO content. When the content of GO was 0.05%, the ultimate load of the beam reached a maximum, which was 39.2% greater than that of the control beam. GO can endow the HSLWC beams with a certain degree of ductility. In addition, a modified JGJ 12-2006 model was proposed to predict the shear capacity of HSLWC beams containing different GO contents on the basis of a comparison of typical models. This study can provide exploratory engineering practice for evaluating and designing GO-reinforced HSLWC structures.